2020
DOI: 10.1128/jb.00154-20
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovismbfNEncodes a Novel LRR Lipoprotein That Undergoes Proteolytic Processing and Binds Host Extracellular Matrix Components

Abstract: Mycoplasma bovis cause serious infection in ruminants leading to huge economic losses. Lipoproteins are key components of mycoplasma membrane and are believed to function in nutrient acquisition, adherence, enzymatic interaction with the host and inducing the host immune response to infection. Genomic data arising from M. bovis show that many of the genes are not assigned any functions, owing in part to their low sequence similarity to those of other bacteria making it difficult to extrapolate gene functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Random transposon mutagenesis combined with phenotypic screening is an efficient method for the characterization of functional genes of the M. bovis . Previous studies have reported enolase, TrmFo, Mbov_0503, and mbfN as adhesion‐related proteins of M. bovi s 19–27 . However, few proteins have been confirmed as cytoadhesion‐related proteins at the bacterial level 19,27 .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Random transposon mutagenesis combined with phenotypic screening is an efficient method for the characterization of functional genes of the M. bovis . Previous studies have reported enolase, TrmFo, Mbov_0503, and mbfN as adhesion‐related proteins of M. bovi s 19–27 . However, few proteins have been confirmed as cytoadhesion‐related proteins at the bacterial level 19,27 .…”
Section: Introductionmentioning
confidence: 95%
“…Bacterial adhesin is a promising candidate for the development of a vaccine against pathogeny 28–30 . Lipoprotein often plays a pivotal role in the pathogenic bacteria to adhere to host cells 13,19,31 . Pathogenic lipoproteins are considered key factors in activating the humoral immune system of the host and are excellent candidate vaccine targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…James and colleagues found that a leucine-rich repetitive lipoprotein (LRR) has adhesin activity ( 43 ). This protein is encoded by the mbfn gene of M. bovis standard strain PG45.…”
Section: Adhesin Of M Bovismentioning
confidence: 99%
“…In addition, this post-translation processing of adhesin is also identified in parasites ( 77 ). In M. bovis adhesins, post-translational processing has also been confirmed ( 43 , 57 ), but the research on this phenomenon is not in-depth. The treatment of adhesin may be closely related to the exposure of adhesin binding sites, immune escape, invasion and toxicity differences.…”
Section: Adhesin Processingmentioning
confidence: 99%